2016
DOI: 10.5586/asbp.3516
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Calamagrostis epigejos expansion on the species composition and soil properties of mountain mesic meadows

Abstract: Due to social and economic changes which have occurred in the last decades, many meadows located in mountain regions have ceased to be used. Abandonment of meadows leads to the degradation of their species composition. An example of degradation may be seen in the development of patches dominated by Calamagrostis epigejos. The aim of this research was to determine the influence of C. epigejos in its consecutive expansion stages on qualitative properties of meadow sward and on selected physico-chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…This problem is especially marked in seminatural grassland managed mainly by mowing (Gloser and Gloser, 1999). In recent years rapid and aggressive expansion of wood small-reed within grassland communities has led to changes in species composition (Stránská, 2004;Kavanová and Gloser, 2005;Holub et al, 2012) and the loss of their previously high species diversity (Pruchniewicz and Żołnierz, 2017). The expansion mechanism of Calamagrostis epigejos and its effects on species composition still remain poorly understood (Pruchniewicz and Żołnierz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is especially marked in seminatural grassland managed mainly by mowing (Gloser and Gloser, 1999). In recent years rapid and aggressive expansion of wood small-reed within grassland communities has led to changes in species composition (Stránská, 2004;Kavanová and Gloser, 2005;Holub et al, 2012) and the loss of their previously high species diversity (Pruchniewicz and Żołnierz, 2017). The expansion mechanism of Calamagrostis epigejos and its effects on species composition still remain poorly understood (Pruchniewicz and Żołnierz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted in mesic meadows degraded by C. epigejos showed positive correlations between the amount of necromass and an increase in the soil's phosphorus and potassium (Pruchniewicz and Żołnierz 2017). However, the stimulating fertilization effect seemed to be inhibited by another mechanism, probably connected with mechanical difficulties in germination.…”
Section: The Influence Of C Epigejos Necromass On Seedling Recruitmementioning
confidence: 86%
“…Previous studies showed an impeding influence of C. epigejos necromass on the species diversity and productivity of mountain grassland habitats (Pruchniewicz and Żołnierz 2017). The negative impact of litter may be connected with its diverse mechanisms of influence.…”
Section: The Influence Of C Epigejos Necromass On Seedling Recruitmementioning
confidence: 95%
See 2 more Smart Citations